FastIoT: an efficient and very fast compression model for displaying a huge volume of IoT data in web environments. (24th December 2021) - Melchiades, Mateus Begnini; Crovato, César David Paredes; Nedel, Everton; Schreiber, Lincoln Vinicius; Righi, Rodigo Da Rosa
Industry 4.0 concept leads to a generation of massive data sets that supervisors must appropriately analyse for an effective decision-making process. A data set, however, can be excessively large, causing troubles when trying to visualise its content entirety. Thus, the present work introduces FastIoT as a novel compression model that focuses on the visual representation of Industry 4.0 data through web environments. As a client-server proposal, FastIoT brings the idea of: (i) speed in data preparation at the server-side, since the proposed method is very simple, and; (ii) efficiency, because we consider the target client plotting area so generating an optimised data set fitted especially for such visual region. Even adding a short time at the server-side for data preparation, with FastIoT we have data ready in the client's display up to 97% faster when compared to traditional plotting methods.